Effect of Auxiliary Engine No. 1 Crankshaft Reconditioning on Lubricating Oil Temperature Rise in MT. SENIPAH - Bayu Putra Pratama (Meteor STIP Marunda, 2023)
This study investigates the effect of crankshaft reconditioning (regrinding/undersizing) on the lubricating oil temperature rise (ΔT) of Auxiliary Engine No. 1 aboard MT. Senipah. A quantitative descriptive field case study approach was employed, comparing thermal performance data before and after the reconditioning process under three load scenarios: 50%, 75%, and 85–90%. Primary data were collected through onboard measurements of lube oil inlet/outlet temperatures, bearing clearances, crankshaft deflection, and journal surface roughness. Secondary data were obtained from the Engine Log Book, workshop reconditioning reports, and manufacturer specifications. Post-reconditioning running tests revealed that the lubricating oil temperature differential (ΔT) remained within the manufacturer’s acceptable limit of 10–12°C across all load conditions, with outlet temperatures consistently below the 75°C normal threshold. The frictional heat generation analysis confirmed that proper clearance restoration and adequate surface finish reduced hydrodynamic friction to within design parameters. A Fishbone (Ishikawa) root cause analysis identified four contributing factor categories—Man, Machine, Material, and Method—to potential post-reconditioning overheating. The study concludes that properly executed crankshaft reconditioning effectively restores thermal stability in the lube oil system, provided that bearing clearances conform to the maker’s undersize chart and a controlled running-in procedure is followed.